2005
DOI: 10.1073/pnas.0503646102
|View full text |Cite
|
Sign up to set email alerts
|

P boutons in lamina IX of the rodent spinal cord express high levels of glutamic acid decarboxylase-65 and originate from cells in deep medial dorsal horn

Abstract: Presynaptic inhibition of primary muscle spindle (group Ia) afferent terminals in motor nuclei of the spinal cord plays an important role in regulating motor output and is produced by a population of GABAergic axon terminals known as P boutons. Despite extensive investigation, the cells that mediate this control have not yet been identified. In this work, we use immunocytochemistry with confocal microscopy and EM to demonstrate that P boutons can be distinguished from other GABAergic terminals in the ventral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
112
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(128 citation statements)
references
References 24 publications
14
112
0
Order By: Relevance
“…In addition, occasional neurons of similar morphology were also observed in lamina IV. These neurons are located in the same region as group I nonreciprocal inhibitory interneurons in the cat Brink et al, 1983;Walmsley, 1991) as well as neurons identified in the mouse that are responsible for presynaptic inhibition of group Ia afferent transmission to motoneurons (i.e., supply P-boutons) (Hughes et al, 2005;Betley et al, 2009). In addition to studying morphological features, we therefore studied whether these GFPϩ neurons have properties similar to either of those populations.…”
Section: Distribution Of Gabaergic Interneurons In Gad65::gfp Micementioning
confidence: 99%
See 3 more Smart Citations
“…In addition, occasional neurons of similar morphology were also observed in lamina IV. These neurons are located in the same region as group I nonreciprocal inhibitory interneurons in the cat Brink et al, 1983;Walmsley, 1991) as well as neurons identified in the mouse that are responsible for presynaptic inhibition of group Ia afferent transmission to motoneurons (i.e., supply P-boutons) (Hughes et al, 2005;Betley et al, 2009). In addition to studying morphological features, we therefore studied whether these GFPϩ neurons have properties similar to either of those populations.…”
Section: Distribution Of Gabaergic Interneurons In Gad65::gfp Micementioning
confidence: 99%
“…However, the group II inhibitory interneurons that project to motoneurons are in intermediate to ventral laminae, are primarily glycinergic, and do not project to Clarke's column. In the region where GFPϩ neurons are located in these GAD65::GFP mice, medial laminae V/VI, there have been two prominent populations of inhibitory neurons previously identified: (1) those responsible for presynaptic inhibition of group Ia afferent synapses on motoneurons (Hughes et al, 2005) and (2) those responsible for nonreciprocal inhibition (Czarkowska et al, 1981;Jankowska et al, 1981;Brink et al, 1983).…”
Section: Inhibitory Interneurons In Medial Laminae V/vimentioning
confidence: 99%
See 2 more Smart Citations
“…Correspondingly, ChAT-IR varicosities, including the C-terminals, and VGluT2-IR boutons did not show evidence of V1 origin. A population of LIX inhibitory boutons with intense GAD65-immunoreactivity corresponds with P boutons (Hughes et al, 2005), the boutons presynaptic to muscle primary afferents in axo-axonal contacts (Conradi, 1969). V1-derived EGFP-IR varicosities in LIX did not correspond with these intensely labeled GAD65-IR terminals (not shown), suggesting that V1-derived interneurons do not give rise to axons involved in this form of presynaptic inhibition.…”
mentioning
confidence: 99%